203k views
2 votes
Solve forn: -6(n-8) = 4(12-5n)+14n

User Clav
by
6.2k points

2 Answers

4 votes

Answer:

0

Explanation:

-6(n-8) = 4(12-5n)+14n

-6(n-8)=-6n+48 = 4(12-5n)+14n= 48-20n+14n

then 48-20n+14n = 48-6n

so you have

-6n+48 = 48-6n

-6n+6n= n

n+48=48

n-48=48-48

n=0

Solve forn: -6(n-8) = 4(12-5n)+14n-example-1
User Lukewestby
by
7.1k points
5 votes


\huge\text{Hey there!}


\huge\text{-6(n - 8) = 4(12 - 5n)}


\huge\text{First, \bf{distribute}}\text{ the terms}

Formula is: a ( b + c) = a(b) + a(c) = ab + ac


\huge\text{First set}\downarrow


\text{-6(n - 8)}\\\text{-6(n) - 6(-8)}\\\text{-6(n) = -6n}\\\text{-6(-8) = 48}\\\boxed{\text{Result for the left side:-6n +48}}


\huge\text{Second set}\downarrow


\text{4(12-n)}\\\text{4(12 - 5n)}\\\text{4(12)-4(-5n)}\\\text{4(12) = 48}\\\text{4(-5n) = -20n}\\\boxed{\text{Result for the right side 48 + (-20)}}


\text{We get:-6n +48 +20n=-20n+ 48+ 20n}

→ = 14n+48 = 48


\huge\text{Now, you have to SUBTRACT by 48 on your}\\\huge\text{sides.}


\text{14n + 48 \bf{ - 48}}\text{ = 48 - \bf{48}}


\text{Cancel out the second: 48 - 48 because it equals 0}


\text{Keep the first one because it helps us solve for our answer}


\text{14n = 0}\\\text{Divide both sides by the number \bf{14}}


\frac{\text{14n}}{14} = (0)/(14)\\\\\text{Cancel out}\frac{\text{14n}}{14}\text{ because it equals to one and we don't need it for this problem}\\\\\\\text{Keep: }(0)/(14)\text{ because it helps us solve for our answer.}


(0)/(14)=0/14 = 0\\\\\boxed{\boxed{\text{Answer: \bf{ n = 0}}}}\checkmark


\text{Good luck on your assignment and enjoy your day!}

~
\frak{LoveYourselfFirst:)}

User GRoutar
by
6.4k points